Catalyst-assisted selective vinylation and methylallylation of a quaternary carbon center using tert-butyl acetate - Mohanta, Nirmala; Samal, Pragnya Paramita; Pandey, Akanksha M.; Mondal, Shankhajit; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2023)
The In-(OTf)(3)-catalyzed & alpha;-vinylationof varioushydroxy-functionalized quaternary carbon centers using in situ generatedisobutylene from tert-butyl acetate is presentedas a novel synthetic methodology. Moreover, tert-butylacetate is a nonflammable feed stock and is a readily available sourcefor the in situ production of vinyl substituents, as demonstratedby the vinylation reaction with quaternary hydroxy/methoxy compounds.Moreover, an excellent selectivity for methylallylation over vinylationwas obtained with Ni-(OTf)(2) as a catalyst. In the case ofperoxyoxindole, methylallyl-functionalized 1,4-benzoxazin-3-one derivativeswere formed through the sequential rearrangement of peroxyoxindolefollowed by the nucleophilic attack by isobutylene. The detailed mechanismfor this reaction and rationalization for the selectivity are providedusing kinetics and density functional theory studies.

Continuous flow β-zeolite catalysed regioselective alkylation of naphthols using alcohols for synthesis of peroxynaphthalen-2(1H)-one, Azidonaphthalen-2(1H)-one and Fluoronaphthalen-2(1H)-one derivatives - Londhe, Gokul; Bokade, Vijay; Gnanaprakasam, Boopathy (Asian Journal of Organic Chemistry, 2025)
Functionalized naphthols are prominent scaffolds in organic synthesis and materials chemistry. Herein, we demonstrated continuous flow alkylation of alpha- and beta-naphthols by using various primary and secondary benzylic alcohols in the presence of environmentally benign granular beta-zeolite as a reusable catalyst. For a variety of beta-naphthols, the respective alkylated products with good regioselectivity were obtained in high yields under mild reaction conditions. This protocol proceeded via the classical Friedel-Crafts type alkylation process and generated stable carbocations as intermediates. Applying this protocol, versatile naphthol derivatives have been synthesized using primary and secondary benzylic alcohols (50 and 44 examples in batch and continuous flow process, respectively), with good yields. Key advantages of this process includes rapid and efficient transformation, facilitates gram-scale synthesis, and generates water as the sole by-product. The most significant advantage is the continuous reusability of granular beta-zeolite, which further emphasizes the sustainability of the method. The application of alkylated naphthols for quaternary functionalization was demonstrated through peroxidation, azidation, and halogenation reactions under the continuous flow module, which yielded the respective peroxynaphthalen-2(1H)-one, azidonaphthalen-2(1H)-one and fluoronaphthalen2(1H)-one derivatives.
Keywords: continuous flow; Multigram Synthesis; Reusable beta-zeolite; Sustainable Appraoch; Transition metal free